Construction and evaluation of RF, SVM, GLM, and XGB machine models. - Hongmin Luo (2142307) (2025)
(A) Boxplots showed the residuals of each machine learning model. Red dot represented the root mean square of residuals (RMSE). (B) ROC analysis of four machine learning models based on 5-fold cross-validation in the testing cohort.